INFORMATION SHARING SYSTEM TO MINIMIZE BULLWHIP EFFECT RISK ON SUPPLY CHAIN MANAGEMENT - ERFANTI FATKHIYAH; Cyrilla Indri Parwati (INTEGER: Journal of Information Technology, 2018)
The process of delivering manufactured products to the hands of consumers, technically the product flow that occurs ie products in the form of finished goods will move from the factory warehouse to the consumer through a series of channels and distribution facilities. This distribution starts from the finished goods warehouse, distribution warehouse, retailer up to the wearer. The existence of various parties involved and coordinate in the flow of products from the factory to the consumer will form a system known as the supply chain system (Pujawan, 2010). Providers of fast products and services, the right time, and the desired conditions while still providing an optimal contribution to the company. Obstacles that are often encountered in the implementation of supply chain is the lack of coordination in terms of sharing information between the chain, thus causing distortion of information and trigger the occurrence of bullwhip effect that is a spike from the actual demand in the consumer level or downstream chain resulting in a very sharp spike at a far level from the upstream consumer or chain. The result of the bullwhip effect is the excess inventory, because demand is much smaller than the demand of the retailers, the unorganized production schedule, the unutilized production facilities optimally, because the production plan still has a high level of speculation. The use of information systems that have not been effective, causing the flow of information to be distorted or distorted, resulting in chaos in the flow of products that occur bullwhip effect and indirectly affect the cash flow of the company. The final result of the research is the application of Web-based Information Sharing System on the distribution channel that can be used efficiently and can provide information deviations that occur between the chains. The hope of stock monitoring results can be used as a control in looking at stock inventory in distributors and retail, so if there is a bullwhip effect, it will appear warning and immediately addressed by the distributor.Keywords: information sharing system, bullwhip effect, distortion of information.